The anthropology of marriage in lowland South America : bending and breaking the rules (University Press of Florida, 2018)
Traditional treatments of marriage among indigenous people focus on what people say about whom one should marry and on rules that anthropologists induce from those statements. This volume is a cultural and social anthropological examination of the ways the indigenous peoples of lowland South America/Amazonia actually choose whom they marry.